Synthesis and Characterization of Polyaniline Coated Carbon Black Composites - Mishra, Sarika; Nigam, A. C.; Gupta, G. S. (IJRDO-Journal of Applied Science, 2017)
Conducting polymer composites are examined universally for their use in variousapplications such as corrosion protection, electromagnetic interference shielding, and Solarcells and corrosion organic light emitting diode. In this coarse, here in, we made a strategyfor homogeneous coating of polyaniline on carbon black for their potential use in differentareas. Polyaniline coated carbon black shows larger surface area, high thermal stability,electrical conductivity and better corrosion resistance. Major application of Carbon black isas reinforcement in automobile tyres where it helps to conduct heat away from the treat andbelt area of the tyre, reducing thermal damage and increasing its life. β–Naphthalenesulphonic acid (β–NSA) was used as surfactant and dopant which offers thehomogeneous coating on carbon black. Polyaniline (PANI)–carbon black composites wereprepared by chemical oxidative polymerization . The SEM of PANI– carbon black alsorevealed the nano porous nature of coating, which can be used for selective incorporation ofother carbon forms. Morphology of PANI– carbon black displays the incorporation of carbon black in PANI matrix. Such prepared conformally polymer coated carbon black could be aauspicious candidate for next generation building block material in several applications.